Determination of Anthocyanin Content of Purple Sweet Potato (Ipomea batatas L) Extract Using the Differential pH Method - Siti Rahmah Kurnia Ramdan; Resi Lestari (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2023)
Purple sweet potato (Ipomea batatas L) is a type of tuber that has many benefits in the food and health .he purple color in sweet potatoes is caused by the presence of anthocyanin purple pigments that spread from the skin to the tuber flesh. The content of sweet potato anthocyanins depends on the intensity of the color of the tubers. The purple the color of the tubers, the higher the anthocyanin content. Anthocyanins have various health benefits, namely as antioxidants, anti diabetic and other benefits, namely as natural dyes.This study aims to determine the levels of anthocyanins in purple sweet potato extract by using Differential pH method. From the research results, it can be concluded that the anthocyanin content of purple sweet potato (Ipomea Batatas L) is 4.26 mg/liter.